PENGEMBANGAN MEDIA PEMBELAJARAN BIOLOGI MATERI KING DOMPLANTAE BERBASIS CANVA UNTUK SISWA KELAS X SMA NEGERI 1 SUSUA - Bu’ulolo, Sektus (TUNAS : Jurnal Pendidikan Biologi, 2024)
This research aims to develop Canva-based learning media that can increase student learning motivation and student learning outcomes. This type of research is research and development (Research and Development) using the 4D development method. The research was tested on 20 class X students of SMA Negeri 1 Susua. To standardize products, it is carried out through three stages of testing, namely practicality and effectiveness testing. The instruments used are research questionnaires and evaluation test questions to determine student learning outcomes. The research results show that this learning media is very valid with a percentage of 89.6% and is suitable for use. The average value of practicality assessed by teachers is 3.5 and 3.3.6 students are in the very practical category. Student motivation results are at 3.36 with an average value of cognitive learning outcomes of 88.7. Based on the results of this research, the Canva-based Kingdom Plantae material biology learning media is stated to be able to increase student motivation and learning outcomes and is a valid, practical learning media. and effective.